Marshall stability properties of asphaltic concrete with kaolin clay under aging - Putra Jaya, Ramadhansyah; M.R., Hainin; H., Awang; K. A., Masri; Intan Suhana, Mohd Razelan; M., Nordiana; A. H., Norhidayah; Y., Haryati; I., Che Ros (IOP Publishing, 2019)
The influence of kaolin clay on marshal stability properties of asphaltic concrete AC14 at different aging conditions was presented in this study. These aging conditions were named as un-aged, short-term, and long-term aging. The conventional asphalt binder of penetration grade 60/70 was used in this investigation. Four different levels of kaolin clay replacement were employed (i.e. 0%, 3%, 6%, and 9% by binder weight). Asphalt concrete mixes were prepared at selected optimum asphalt content (5%). The performance was evaluated based on Marshall Stability and voids characteristics. Results indicated the improving stability performance that the mixes modified with kaolin clay have under aging conditions. The result also showed that the use of 6% to 9% kaolin clay can produce more durable asphalt concrete mixtures with better serviceability.